1997
DOI: 10.1002/(sici)1099-0720(199702)11:1<3::aid-acp422>3.3.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

Accusations by Adults of Childhood Sexual Abuse: a Survey of the Members of the British False Memory Society (BFMS)

Abstract: SUMMARYMembers of the British False Memory Society (BFMS) were sent a detailed questionnaire concerning accused families and 282 (70%) replied. In this paper the author focuses on the nature, circumstances, and consequences of the accusations for the accused, as well as the role of therapy. The great majority (87%) of the accusers were female and most of the accusations were directed against the biological father. Only four per cent involved stepfathers. Often the accusations were non-specific and not all were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 9 publications
1
8
0
Order By: Relevance
“…This is unlikely to be the case and de Rivera oversimplifies the reality of the situation. In my study of BFMS members (Gudjonsson, 1997a(Gudjonsson, , 1997b(Gudjonsson, , 1997c, several families stated that their case did not allegedly involve recovered memories and sometimes the memories emerged without therapy. In many other cases, the families did not even know whether the accusations were associated with recovered memories and therapy.…”
Section: Some Methodological Issuessupporting
confidence: 86%
See 4 more Smart Citations
“…This is unlikely to be the case and de Rivera oversimplifies the reality of the situation. In my study of BFMS members (Gudjonsson, 1997a(Gudjonsson, , 1997b(Gudjonsson, , 1997c, several families stated that their case did not allegedly involve recovered memories and sometimes the memories emerged without therapy. In many other cases, the families did not even know whether the accusations were associated with recovered memories and therapy.…”
Section: Some Methodological Issuessupporting
confidence: 86%
“…Indeed, we have no way of knowing from the article whether the cases selected are representative of the more than 300 retractors referred to in the article out of a total of 5,85 1 cases from the files of the False Memory Syndrome Foundation (FMSF). This represents a retraction rate of 5%, which is similar to that found in a recent study I conducted (Gudjonsson, 1997a) of 282 members of the British False Memory Society (BFMS). I found that 4% of the accusers had retracted all the accusations and a further 5% had retracted some of the accusations.…”
Section: Some Methodological Issuesmentioning
confidence: 97%
See 3 more Smart Citations